Solve equation $\sqrt{4t + 1} = 3-3t$

→ I squared both sides and got ► $4t + 1 = 9 - 18t- 3t²$

→ I then moved the 3t² to the left side and combined like pairs and got ► $3t² + 12t - 8 = 0$

I'm stuck at that point. Can someone tell me what I am doing wrong?

  • $\begingroup$ $4t+18t=22t$, is that troubling you? $\endgroup$ – Inceptio May 17 '13 at 8:27
  • $\begingroup$ When you square the right, you should get $9-18t+9t^2$ Then when you combine the two sides you should have $22t$, not $12t$ $\endgroup$ – Ross Millikan May 17 '13 at 18:23

For starters, squaring $\sqrt{4t+1}=3-3t$ gives $4t+1=9-18t+9t^2$. A little rearranging and we have $9t^2-22t+8=0$.

With a bit of insight we can see that this is $(9x-4)(x-2)$.

However, I'm pretty crap at factoring so lets use the quadratic formula:

$$ax^2+bx+c=0$$ implies

$$x=\frac{-b \pm \sqrt{b^2-4ac}}{2a}$$

So we take $$x=\frac{-(-22)\pm\sqrt{22^2-4(9)(8)}}{2(9)}$$ now step-by-step we have

$$x=\frac{22\pm\sqrt{484-288}}{18}=\frac{22\pm\sqrt{196}}{18}=\frac{22\pm14}{18} =\frac{11\pm7}{9}$$ So for "$+$" we have $x=\frac{18}{9}=2$ and for "$-$" we have $x=\frac 4 9$.

  • 2
    $\begingroup$ I think its also quickly worth mentioning that this only shows that if $\sqrt{4t+1}=3-3t$, then $9t^2-22t+8=0$ - i.e. that a solution of the quadratic is not necessarily a solution to the original equation, so you still need to check. $\endgroup$ – Andrew D May 17 '13 at 8:47
  • $\begingroup$ Thanks so much! I usually use this formula: x^2 + px + q thus x = p/2 ± √ (p/2)^2 - q Will have to memorize this formula. I guess it's quicker way to solving problems such as these. $\endgroup$ – Kalina Kama May 17 '13 at 9:38

You made a mistake in squaring the right hand side: $$ (3-3t)^2=9-18t+9t^2 $$ However you have also to impose the condition $3-3t\ge0$, because the left hand side is non negative by definition. So you get

$$ 9t^2-22t+8=0,\qquad t\le1 $$

The quadratic equation has roots $2$ and $4/9$, as it's easy to see. Hence the unique solution to your equation is $t=4/9$.

If you "back substitute", you can understand what happens: for $t=2$ the left hand side is $\sqrt{4\cdot2+1}=3$, while the right hand side is $3-3\cdot2=-3$.

For $t=4/9$, the left hand side is $\sqrt{16/9+1}=5/3$, and the right hand side is $3-3\cdot(4/9)=3-4/3=5/3$.

The problem is that upon squaring you also add the solutions to $\sqrt{4t+1}=-(3-3t)$ that is another equation.



If $ax^2+bx+c=0$, $\displaystyle x=\frac{-b\pm\sqrt{b^2-4ac}}{2a}$.


Given: $\sqrt{4t+1}=3-3t$







Which is a quadratic in the form:$$0 =ax^2+bx+c$$ Use the quadratic equation: $$x=\frac{-b \pm \sqrt{b^2-4ac}}{2a}$$

$$x = \frac{ -(-22)\pm \sqrt{(-22)^2-4(9)(8)}}{2(9)}$$

$$x = \frac{22\pm\sqrt{484-288}}{18}$$

$$x = \frac{22\pm\sqrt{196}}{18}$$

$$x = \frac{22\pm{14}}{18}$$

$$x = 2 $$ $$or$$ $$x =\frac{4}{9} $$

Understand that it still be checked that these are indeed solutions to your initial equation.

  • $\begingroup$ Of course $2$ is not a solution for the original equation, because $\sqrt{9}\ne3-3\cdot2$. $\endgroup$ – egreg May 17 '13 at 17:22

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.